Off-pump coronary artery bypass grafting in high-risk patients: a review - Guida, Gustavo A.; Chivasso, Pierpaolo; Fudulu, Daniel; Rapetto, Filippo; Sedmakov, Christo; Marsico, Roberto; Zakkar, Mustafa; Bryan, Alan J.; Angelini, Gianni D. (Journal of Thoracic Disease, 2016)
The role of off-pump coronary artery bypass (OPCAB) grafting in high risk patients remains controversial. While there have been studies showing the potential benefits of it, there is still a lot to be learned from the application of this technique in this sub-group of patients. The results of the different trials and papers that we reviewed seem to indicate a benefit in the OPCAB group. Despite of the fact that trials were significantly different in methodology, especially when choosing the risk score stratification tool or the cut-off to define high risk the literature seems to suggest a benefit from the use of OPCAB surgery. Here, we present a review which focussed on early and late outcome in high risk patients undergoing on- and offpump coronary revascularization.